[ ] > >
   
   



 
 
  
06-06-2008, 11:36 PM   #11

goooga

 
: Apr 2008
:
:
:
:
: 562







( ) = ( )



:::

() () :

: = 2ߑ2 - 3 - 15
: =ߑ2 - 2 - 3





(( ))

=

2ߑ2 - 3 - 15= ߑ2 - 2 - 3

(ߑ2) ()

2ߑ2 - ߑ2 = ߑ2 (( ߑ2 -



- 3 + 2= - (( -2 +

-15 +3= 12 (( -3 + 3



ߑ2 - - 12

ߑ2 - - 12 = 0






= - +_ ȑ2 - 4

2

ߑ2 - - 12= 0

()= 1 (ߑ2)
()=-1 ()
()= -12 (-12)


= -(-1)+ (-1)2- 41-12

21

= +1 + 1 - (-48)

2

- -1=1 -
-1 =1
41-12=-48


= 1+ 1+48 (( + 1- -48 +

2

= 1+ 49

2

= 1+ 7 (( 7 49 = 7 ))

2

= 1+72= 4

4



= ߑ2 - 2 -3

= 42 - 24 - 3 = 16- 8-3= 5


 

goooga    
 

 

« | »
:




 

 


12:38 PM

- [ ] - -

Powered by vBulletin® Version 3.8.9 Beta 3
Copyright ©2000 - 2017, vBulletin Solutions, Inc.
Ads Organizer 3.0.3 by Analytics - Distance Education

2003-2017